The importance of the assessment of natural concentration of Pb in soils of the State of Minas Gerais (Research, Society and Development, 2020)
The increase in the concentrations of trace elements in soil can occur either due to anthropogenic activities or due to natural processes. The aim of this study was to investigate the natural concentration of lead (Pb) in soils in the Minas Gerais State and compare with the guiding values advocated in CONAMA Resolution No. 420, 2009. This work can be used for managing the Stat’s Metal Mines and inform the public of the likely risks that are subordinate. To support this work were used the Soil Map of Minas Gerais and the MG Geological Map. In Minas Gerais, there is not a prevalence of disturbed areas with Pb below the VRQ, and only six areas showed potential for natural contamination, justified by geology and soil class in each region.